Parapharyngeal tumor simulates a peritonsillar abscess. Clinical case - Halawa, Wasim Elhendi (2011)
As a result of a clinical case in which it was easy to confuse an infectious - inflammatory process of the peritonsillar region with a tumor of the parapharyngeal space, the authors performed a revision of the literature about the clinic features that tumors of this region usually present during physical exploration. The aim was to alert E.N.T. specialists about considering the differential diagnosis of pathologies that commonly affect this region, before initiating any therapeutic initiative which may have undesirable results.